2023
DOI: 10.3389/fimmu.2023.1161522
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional and single-cell sequencing of liver cancer reveals comprehensive host-virus interactions in HBV infection

Abstract: BackgroundsHepatitis B virus (HBV) infection is a major risk factor for chronic liver diseases and liver cancer (mainly hepatocellular carcinoma, HCC), while the underlying mechanisms and host-virus interactions are still largely elusive.MethodsWe applied HiC sequencing to HepG2 (HBV-) and HepG2-2.2.15 (HBV+) cell lines and combined them with public HCC single-cell RNA-seq data, HCC bulk RNA-seq data, and both genomic and epigenomic ChIP-seq data to reveal potential disease mechanisms of HBV infection and host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Interestingly, we found most of these VIMs (12/14) resided in the boundaries of chromosome TADs in HepG2 liver cancer cells (TAD information downloaded from Wang et al 18 ) (Supporting Information: Figure ). We further found that HBV integration events also tended to happen within TAD boundaries ( p value = 3.9e‐9, odds ratio = 1.45, see Section 2), which was consistent with our recent report 28 …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, we found most of these VIMs (12/14) resided in the boundaries of chromosome TADs in HepG2 liver cancer cells (TAD information downloaded from Wang et al 18 ) (Supporting Information: Figure ). We further found that HBV integration events also tended to happen within TAD boundaries ( p value = 3.9e‐9, odds ratio = 1.45, see Section 2), which was consistent with our recent report 28 …”
Section: Resultssupporting
confidence: 92%
“…We further found that HBV integration events also tended to happen within TAD boundaries (p value = 3.9e-9, odds ratio = 1.45, see Section 2), which was consistent with our recent report. 28 Mutations in TAD boundaries were known to cause gene regulatory network rewiring and abnormal expression of oncogenes. 29,30 We further investigated whether any TF binding was enriched in these risk regions by integrating binding peaks from >1100 TFs.…”
Section: Increased Hbv Mutation Diversity In Tumors Without Hbv Integ...mentioning
confidence: 99%
“…During this process, there are dynamic changes in the A/B compartments, mainly in the genomic regions on chromosomes 9, 13, and 21. Most genes are moved from transcriptionally repressed B compartments to A compartments, where they are subsequently activated 256 . These regions have many transposable elements that promote viral DNA replication.…”
Section: D Genome Structural Variations and Diseasementioning
confidence: 99%
“…Using Hi-C sequencing, Guo et al analysed chromatin interactions in a HBV-infected human hepatoma cell line and its uninfected counterpart ( Guo et al, 2023 ). They observed enhanced chromatin interactions, especially on distinct interphase chromosomes, in HBV-positive cells and recorded characteristic shifts in nuclear subcompartments, accompanied with repression of enhancers regulating inflammatory genes and opening of regions enriched in transposable elements ( Guo et al, 2023 ). These data suggested that reorganization of 3D genome structure may contribute to disease development associated with HBV infection.…”
Section: Chromatin Reorganization In Hepatitis B Virus (Hbv) Infected...mentioning
confidence: 99%